Kesenjangan Komunikasi Kebijakan PP Tunas: Antara Idealita Regulasi dan Realitas Perlindungan Anak Digital - Anna Nurjanah; Sri Hesti; Rengga Sendrian; Akmal Widji Nursalim; Anggun Rinenggo; Aufa Fawazkani; Revilla Tirana Oulina (Asosiasi Dosen Muda Indonesia, 2026)
The escalation of digital risks confronting children has prompted the issuance of Government Regulation No. 17 of 2025 on the Governance of Electronic System Operation in Child Protection (PP TUNAS). Nevertheless, its field effectiveness remains hindered by challenges in information dissemination and the technical readiness of digital platforms. This study aims to explore in depth the perceptions, experiences, and practices of urban communities in conceptualizing PP TUNAS, while identifying the discrepancy between regulatory frameworks and the reality of child protection from a policy communication perspective. To analyze this phenomenon, a qualitative approach utilizing an interpretive case study design was employed. Primary data were gathered through semi-structured in-depth interviews with key informants—comprising parents, educators, and digital literacy advocates in urban areas—and complemented by observation alongside secondary survey data from the Evident Institute for methodological triangulation. Thematic analysis reveals that while urban communities overwhelmingly support the age-restriction mandate, their understanding remains superficially normative due to an underlying policy communication gap. Furthermore, a structural implementation gap emerged, as platform age-verification mechanisms are perceived as highly susceptible to bypass. In response to these technical shortfalls, parents and schools have independently adopted localized digital parental mediation strategies, despite lacking formal integration with the legal framework. This study concludes that the success of PP TUNAS cannot rest solely on judicial enforcement; rather, it necessitates robust platform technical infrastructure, comprehensive public policy communication strategies, and an integrated orchestration of multi-stakeholder governance.